Daily field checking list by Walter Rosene, May 18, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 18, 1936. This checklist was used by Walter Rosene to record birds sighted around North Bridge, Heitkamp Pond and Boxholm Pond between 9:00 and 9:30. Plustek--flatbed